Asphalt modification using thermoplastic polymer components - Roy O. Anabo (International Research Journal of Science, Technology, Education, and Management)
Asphalt modification using thermoplastic polymer components a plastic waste turned into an innovative product, environmentally friendly, and cost-effective. Plastics, specifically thermoplastics have many uses but with the increasing population, consumption of plastic is rampant. To come up with innovative solutions that can be used to minimize plastic and create usage in construction highways, buildings, and houses is the main concern in this study. Therefore, the study aimed to find innovative solutions using plastic waste that can use thermoplastics as an asphalt modification. An experimental research method was used to determine the acceptability and predict what may occur. Based on the findings of the actual observations made from two set-ups (Modified Asphalt and Unmodified Asphalt) it was found the results of acceptability data in the utilization of thermoplastic polymer components under set-up a got a final mean score of 3.9. However, set-up b provided the best result with the highest acceptability mean score of 4.8. Therefore, using thermoplastic polymer components in terms of texture, strength/durability, and soundness is highly acceptable. The cost of modified asphalt amounted to Php 10.00; it shows positively that the use of thermoplastics for modifying asphalt pavement is not costly but rather cheap. Utilization of recycled thermoplastic polymers as an asphalt modification will contribute strength of the pavements, help to attain sustainability in reducing plastic waste, and friendly environment innovation techniques. A highly recommended follow-up marshall-stability testing was conducted to have more reliable results regarding the strength/durability, modulus of elasticity, and rupture of the asphalt.